The mechanism and effect of repetitive transcranial magnetic stimulation for post-stroke pain - Pan, Long-Jin; Zhu, Hui-Qi; Zhang, Xin-An; Wang, Xue-Qiang (Frontiers in Molecular Neuroscience, 2023)
Post-stroke pain (PSP) is a common complication after stroke and affects patients' quality of life. Currently, drug therapy and non-invasive brain stimulation are common treatments for PSP. Given the poor efficacy of drug therapy and various side effects, non-invasive brain stimulation, such as repetitive transcranial magnetic stimulation (rTMS), has been accepted by many patients and attracted the attention of many researchers because of its non-invasive and painless nature. This article reviews the therapeutic effect of rTMS on PSP and discusses the possible mechanisms. In general, rTMS has a good therapeutic effect on PSP. Possible mechanisms of its analgesia include altering cortical excitability and synaptic plasticity, modulating the release of related neurotransmitters, and affecting the structural and functional connectivity of brain regions involved in pain processing and modulation. At present, studies on the mechanism of rTMS in the treatment of PSP are lacking, so we hope this review can provide a theoretical basis for future mechanism studies.